2021
DOI: 10.1186/s12889-021-12069-w
|View full text |Cite|
|
Sign up to set email alerts
|

Home environment and noise disturbance in a national sample of multi-family buildings in Sweden-associations with medical symptoms

Abstract: Background Poor acoustic conditions at home can have negative health impact. The aim was to investigate home environment factors and medical symptoms associated with noise disturbance. Methods All adults (≥18 y) registered in selected apartments in Sweden were invited to participate in a questionnaire survey including medical questions and personal factors. Totally 5775 adults participated (response rate 46%). Information on home environment was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
(37 reference statements)
0
12
0
Order By: Relevance
“…The threshold of perceived annoyances would probably vary by individual, e.g., women have a lower threshold for detection of odor and thermal discomfort, while older people have a higher threshold [ 14 , 26 ]. Likewise, smokers have been reported to have a higher odor threshold [ 14 , 26 ], and young people report annoyances from noise more often compared to older people [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The threshold of perceived annoyances would probably vary by individual, e.g., women have a lower threshold for detection of odor and thermal discomfort, while older people have a higher threshold [ 14 , 26 ]. Likewise, smokers have been reported to have a higher odor threshold [ 14 , 26 ], and young people report annoyances from noise more often compared to older people [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Regarding airtightness, apartment buildings are more airtight than detached houses, resulting in increased condensation, mold, and dampness. 20 The Swedish BETSI (Building, Energy use, Technical Status, and Indoor environment) study [3][4][5][6][7] surveyed 5775 adults aged 18 years and older living in apartments (4369 households) and found that these factors (dampness, mold, and condensation), especially in rental apartments, increase the risk of rhinitis, asthma, and respiratory infections 3 as well as the risk of eye, nose, throat, and skin symptoms, headaches, and fatigue. 6 In addition, because the residential environment of apartments varies depending on the location of units and number of floors in a building, there are several issues that do not exist in detached houses.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale surveys have provided important insights into the relationship between housing and the health status of residents in countries such as New Zealand, Sweden, and Japan. [1][2][3][4][5][6][7][8][9][10][11] The World Health Organization (WHO) published the WHO Housing and Health Guidelines 12 in 2018, recommending improvements in the living environment based on these previous studies. The guidelines state that improved housing can reduce disease, improve quality of life, and contribute to the achievement of many Sustainable Development Goals (SDGs), including SDG 3 (Good Health and Well-Being) and SDG 11 (Sustainable Cities and Communities).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original [ 1 ] publication of this paper figures 2 and 4 were swapped, the captions and citations were correct. The article has been updated with the correct figures.…”
mentioning
confidence: 99%